Hydrogen-rich water improves endurance by reducing skeletal muscle oxidative stress and inflammatory responses - Mizuno, Eika; Sato, Tatsuhiro; Okada, Kosuke; Miura, Ikuru; Shoda, Junichi; Saito, Makoto; Mori, Yutaro; Oh, Sechang; Isobe, Tomonori (Frontiers in Nutrition, 2026)
IntroductionHydrogen-rich water (HRW) has been reported to reduce oxidative stress, suppress exercise fatigue, and enhance recovery. However, the molecular mechanisms of its effects on exercise capacity, especially during the early stages of adaptation in physically inactive individuals, remain unclear.MethodsMale 8-week-old C57BL/6 J mice were provided with purified water or HRW for 1, 2, 4, or 6 weeks. Their exercise endurance was assessed using treadmill running distance, and their levels of markers of oxidative stress, inflammation, and muscle damage were analyzed in skeletal muscle at baseline and after exercise at each time point.ResultsMice that consumed HRW for ≥P4 weeks ran significantly longer distances, showed less muscle fatigue, and had lower levels of markers of oxidative stress, inflammation, and muscle damage. Notably, antioxidant gene expression was not high, despite the lower level of oxidative stress, suggesting the possibility that HRW directly scavenges or suppresses reactive oxygen species, independently of antioxidant pathways.DiscussionHRW consumption alleviates oxidative stress and inflammation in skeletal muscle and improves exercise endurance. These findings suggest that the administration of HRW may represent a promising antioxidant strategy to support the initiation of and compliance with exercise programs by physically inactive individuals.